String theory : David Foster Wallace on tennis - Wallace, David Foster ([Library of America], 2016)
Collects essays about tennis in which the author challenges the sports memoir genre, profiles two of the world's greatest players, and shares his own experiences in his youth as a regionally ranked tennis player.